A new species of Metron Godman, 1900 (Lepidoptera, Hesperiidae) from the western Amazon, with a unique hindwing color pattern in Hesperiina, its phylogenetic placement, and an illustrated key for the genus - Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins; Grishin, Nick V. (Zootaxa, 2024)
Metron mentor Dolibaina, O. Mielke & Casagrande, sp. nov. is described from the western Amazon of Brazil, Peru, and Venezuela. The wide white area covering part of the hindwing and body of the new species is unique in Hesperiina and is hypothesized to create a disruptive pattern when the insect is at rest, resembling a bird dropping. Based on genomic data, Metron mentor sp. nov. is recovered as a sister species of all the known species of Metron Godman, 1900. This hypothesis suggests that the similar ventral hindwing of M. mentor sp. nov. to species formerly in Metron and Propertius Evans, 1955, but currently in Metrocles Godman, 1900 may be plesiomorphic. The new species is illustrated and described, a phylogenomic hypothesis for Metron is presented, and an illustrated key for both sexes (when known) is given for all the species and subspecies in the genus.